Jacob Kingsbury papers - Kingsbury, Jacob, 1756-1837.
Chiefly correspondence, together with deeds and land records of the Hartshorn family of Norwich, Conn., military reports, memoranda, inventories, garrison orders, general orders, court-martial proceedings, guard mounts at Fort Walcott (1812), countersign book (1813), and inspection returns (1814). Prominent correspondents include Thomas Humphrey Cushing, John Pratt, Horatio Stark, Elisha Tracy, and James Wilkinson.
U.S. Army officer.
Collection material in English.
Keywords: Cushing, Thomas, -- 1725-1788 -- Correspondence; Pratt, John, -- 1753-1824 -- Correspondence; Stark, Horatio -- Correspondence; Tracy, Elisha, -- 1766-1846 -- Correspondence; Wilkinson, James, -- 1757-1825 -- Correspondence; Hartshorn family; United States. -- Army -- History; Courts-martial and courts of inquiry -- United States; Deeds -- Connecticut -- Norwich; Fortification -- Rhode Island; Land tenure -- Connecticut; Fort Walcott (R.I.); Norwich (Conn.) -- History; United States -- History -- War of 1812.; Army officers